Survey record of lac insect Kerria lacca and its host plants in western plains of India - MEENA, S C; SHARMA, K K; SWAMI, H; RANA, B S; LEKHA, LEKHA; LOHOT, V D (The Indian Journal of Agricultural Sciences, 2020)
The low infiltration capacity of sodic soils and alkaline irrigation water are the main limiting factors in sustaining crop production under salt affected agro-ecosystems. The extreme rains aggravate the chances of crop failure further, due to water stagnation for prolonged period under sodic lands. Frequency of such extreme rainfall events is likely to increase in near future due to changing climatic scenario. ICAR-Central Soil Salinity Research Institute, Karnal, designed, developed and installed the cavity type individual farmer’s based recharge structure at four locations in low lying areas of adopted villages (under Farmer FIRST Project) of Kaithal district for evaluating their effectiveness in facilitating the localized drainage option and sustainable crop production. The study results indicated that the installed structures were quite effective in saving the submerged crops particularly during the periods of intense rain in addition to augmenting groundwater and improving its quality. The groundwater table rose to an extent of 2-3 m beneath the structure during monsoon month (July 2017) compared to summer month of April 2017. The improvement in groundwater quality was also observed in surrounding areas as a consequence of reduction in RSC by 2-3 meq/l compared to the values at the time of installation of the structure. A heavy rainfall (~150 mm) resulted in 35-40% crop damage in open-fields which was reduced down to 5-15% due to provision of recharge structure, significantly decreasing the additional cost towards re-transplanting and compensated the yield loss. Benefit-cost ratio of 1.93 and internal rate of return of 145% indicated economic feasibility of the investment on recharge structure. The results revealed that installation of recharge structure was quite advantageous in providing the localized drainage option in low lying and land locked areas where runoff gets accumulated and adversely affected the crop production.